Synthesis of Dihydro-1,4-oxathiins by Rearrangement of 1,3-Oxathiolane Sulfoxides - 한호규; 남기달; Lee Wha Suk (AMER CHEMICAL SOC, 1986)
A new synthesis of 5,6-dihydro-2-methyl-1,4-oxathiin-3-carboxylic acid derivatives by ring expansion of corresponding 1,3-oxathiolane 3-oxides is described. Oxidation of 2-methyl-N-phenyl-1,3-oxathiolane-2-acetamide (7a) and 2-methyl-1,3-oxathiolane-2-acetic acid methyl ester (7b) gave a mixture of cis and trans sulfoxides 8 and 9, major and minor, respectively. Assignments of the cis and trans sulfoxides were based on the aromatic solvent induced